2022
DOI: 10.1111/jocn.16405
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory study of fathers providing Kangaroo Care in a Neonatal Intensive Care Unit

Abstract: Aim and Objectives: To explore fathers' views and experiences of providing Kangaroo Care (KC) to their baby cared for in a Neonatal Intensive Care Unit (NICU).Background: Kangaroo Care has been known to improve the health outcome for preterm, low birth weight and medically vulnerable term infants and achieve the optimal perinatal health wellbeing for parents and infants. Historically, mothers are considered as the dominant KC providers, whereas fathers are spectators and have been overlooked. Little is known a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
(57 reference statements)
0
3
0
1
Order By: Relevance
“…Another qualitative study from Australia showed that fathers perceived positive experiences of SSC in the NICU setting. Fathers perceived SSC enhanced their bonding and attachment with their babies [ 38 ]. Another study from Turkey found that fathers' SSC improved babies' physiological parameters and stability [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another qualitative study from Australia showed that fathers perceived positive experiences of SSC in the NICU setting. Fathers perceived SSC enhanced their bonding and attachment with their babies [ 38 ]. Another study from Turkey found that fathers' SSC improved babies' physiological parameters and stability [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, several studies have assessed the positive impact of SSC on the outcomes of babies and fathers [31,[37][38][39]. A study examining the effect of SSC between fathers and newborns on the attachment relationship in northern Taiwan found a higher significant attachment score (measured by the Father-Child Attachment Scale) in fathers who practiced SSC compared to those who did not [37].…”
Section: Discussionmentioning
confidence: 99%
“…38 Furthermore, where kangaroo care is commenced within 24 hours of birth (rather than delaying beyond this point), there is a reduction in nosocomial sepsis and hypothermia. 38 Kangaroo care improves parent-infant bonding and increases parental confidence in looking after their infant 41,42 ; it has also been shown to reduce severe postnatal depression. 42 A longer-term follow-up of infants who participated in randomized controlled trials of kangaroo care demonstrated better neurological, behavioral, and education outcomes in children who had kangaroo care than those who did not.…”
Section: The Evidencementioning
confidence: 99%
“…O ALCON é um ambiente que favorece a não separação entre mãe e bebê no período pós-parto, estimula o aleitamento materno desde o nascimento até a alta hospitalar e influencia no sucesso da amamentação após a alta (6) . Destaca-se que, além da mãe, o pai pode realizar a posição canguru com seu filho e receber benefícios dessa prática, como o aumento do apego e vínculo entre pais e filhos (7) .…”
Section: Introductionunclassified